2013
DOI: 10.1039/c3ob27464k
|View full text |Cite
|
Sign up to set email alerts
|

The role of imidazole in peptide cyclization by transesterification: parallels to the catalytic triads of serine proteases

Abstract: The improved bioavailability, stability and selectivity of cyclic peptides over their linear counterparts make them attractive structures in the design and discovery of novel therapeutics. In our previous work, we developed an imidazole-promoted preparation of cyclic depsipeptides in which we observed that increasing the concentration of imidazole resulted in the concomitant increase in the yield of cyclic product and reduction in dimerization, but also resulted in the generation of an acyl-substituted side pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 52 publications
0
19
0
1
Order By: Relevance
“…This mechanism is similar to the histidine-serine portion of the catalytic triad in serine proteases. 26 Free imidazole showed a much lower catalytic activity compared to peptide nanofibers, which illustrates the importance of histidine residue organization in the nanofibrous system ( Figure 2). Preorganization of a supramolecular system containing high densities of histidine residues increases the efficiency of catalysis compared to free and dispersed imidazole.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…This mechanism is similar to the histidine-serine portion of the catalytic triad in serine proteases. 26 Free imidazole showed a much lower catalytic activity compared to peptide nanofibers, which illustrates the importance of histidine residue organization in the nanofibrous system ( Figure 2). Preorganization of a supramolecular system containing high densities of histidine residues increases the efficiency of catalysis compared to free and dispersed imidazole.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Although the interaction with 1 proceeded at much slower rate in this case, the addition of imidazole could improve the interaction rate (Figure d). This indicated the involvement of the imidazole group as a proton transfer catalyst in the overall sensing process . Nevertheless, the extent of spectral change observed in this case was less (ca.…”
Section: Resultsmentioning
confidence: 78%
“…This indicated the involvement of the imidazole group as ap roton transfer catalyst in the overall sensing process. [38,39] Nevertheless, the extent of spectral change observed in this case was less (ca. 2.25 fold) than for histamine ( Figure 2b), which indicated that there must be an additional role played by the imidazole group in the overall sensing process.…”
Section: Investigation Of the Mode Of Interaction With Histaminementioning
confidence: 71%
“…VIm could donate its lone sp 2 electron pair to a vacant boron p orbital in borax to form an amine–boron complex 95,96 . Imidazole, which can catalyze esterification reactions, 97 could also promote the esterification of the α ‐carbonyl aldehyde generated during HTC and thus interfere with the HTC process 91,98 . In addition, the formation of imidazole anions in the alkaline solution could promote salt formation and precipitation 99 .…”
Section: Resultsmentioning
confidence: 99%